Environmental surface sampling for SARS-CoV-2 around hospitalized patients with COVID-19 in a tertiary care hospital - Goel, Varun; Gupta, Savita; Gupta, Vivek; Sahni, Ajay Kumar (Asian Journal of Medical Sciences, 2022)
Background: The contamination of patients’ surroundings by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains understudied. Discordant findings of SARS-CoV-2 RNA in environmental samples were noted in many reports. Aims and Objectives: The study assessed the extent and persistence of environmental surface contamination in real-world surfaces around COVID-19 patients. Materials and Methods: We sampled the surroundings of two intensive care unit (ICU) and one ward that were occupied by laboratory-confirmed coronavirus disease 2019 (COVID-19) patients. Frequently touched environmental surfaces near patients were swabbed before and after daily environmental disinfection. Results: Of 355 environmental samples, 6 (1.69%) were positive by real-time reverse-transcription polymerase chain reaction assay. Among those, 5 of 75 ICU samples (6.67%) and 1 of 75 ward environmental samples (1.33%) in the pre-fumigation areas occupied by COVID-19 positive patients were positive. No samples obtained within the first 2 h of fumigation and surface disinfection was found to be positive. Conclusion: Surrounding environment of symptomatic COVID-19 patients can get contaminated and in cases of asymptomatic COVID-19 patients, contamination of their surroundings was an uncommon phenomenon. Strict contact barrier precaution, routine cleaning with disinfectants are mandatory hospital infection control practices in the management of patients infected with SARS-CoV-2.